New initiatives for sustainable food: A case study of an organic producer cooperative - Gill Seyfang (University of East Anglia, The Centre for Social and Economic Research on the Global Environment (CSERGE), 2004)
Sustainable consumption is gaining currency as a new environmental policy objective. This paper applies 'new economics' theory to evaluate a local organic food initiative as a tool for 'alternative' sustainable consumption, which is here understood to mean redefining social infrastructure and systems of provision to enable a reduction in consumption levels and hence a reduced ecological footprint. The rationales for localised organic food systems is: increasing local self-reliance, farmers' response to vulnerability to negative impacts of globalisation, avoiding pesticides, cutting food miles and associated energy use, and re-embedding food provisioning within local communities. A case study local organic producer cooperative is found to be successfully achieving its aims of providing a fair, ecological, cooperative food system. It overcomes the limitations of mainstream strategies for sustainable consumption, and goes further in developing new social and economic institutions. It uses food as a mechanism for community-building and social cohesion, while delivering sustainable rural livelihoods and a channel for the expression of alternative values about society, environment and the economy. Internal and external barriers to the growth of this initiative include the need to widen appeal and recruit more producers and public procurement policy and current pricing regimes. Government action is needed to support the growth of such 'alternative' sustainable consumption initiatives and policy recommendations are made.
Keywords: 330; agri-food networks; cooperatives; governance; local food; organic food; sustainability; Biokost; Alternative Ökonomie; Tauschwirtschaft; Einkaufsgenossenschaft